Comparison of 2-year clinical outcomes between diabetic versus nondiabetic patients with acute myocardial infarction after 1-month stabilization: Analysis of the prospective registry of DIAMOND (DIabetic acute myocardial infarctiON Disease) in Korea: an observational registry study. Issue 25 (June 2016) - Hur, Seung-Ho; Won, Ki-Bum; Kim, In-Cheol; Bae, Jang-Ho; Choi, Dong-Ju; Ahn, Young-Keun; Park, Jong-Seon; Kim, Hyo-Soo; Choi, Rak-Kyeong; Choi, Donghoon; Kim, Joon-Hong; Han, Kyoo-Rok; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This study assessed the 2-year clinical outcomes of patients with diabetes mellitus (DM) after acute myocardial infarction (AMI) in a cohort of the DIAMOND (DIabetic Acute Myocardial infarctiON Disease) registry. Clinical outcomes were compared between 1088 diabetic AMI patients in the DIAMOND registry after stabilization of MI and 1088 nondiabetic AMI patients from the KORMI (Korean AMI) registry after 1 : 1 propensity score matching using traditional cardiovascular risk factors. Stabilized patients were defined as patients who did not have any clinical events within 1 month after AMI. Primary outcomes were the 2-year rate of major adverse cardiac events (MACEs), a composite of all-cause death, recurrent MI (re-MI), and target vessel revascularization (TVR). Matched comparisons revealed that diabetic patients exhibited significantly lower left ventricular ejection fraction (LVEF) and estimated glomerular filtration rate and smaller stent size. Diabetic patients exhibited significantly higher 2-year rates of MACE (8.0% vs 3.7%), all-cause death (3.9% vs 1.4%), re-MI (2.8% vs 1.2%), and TVR (3.5% vs 1.3%) than nondiabetic patients (all P  < 0.01), and higher cumulative rates in Kaplan–Meier analyses of MACE, all-cause death, and TVR (all P  < 0.05). A multivariate Cox regression analysis revealed that chronic kidney disease, LVEF < 35%, and long stent were independent predictors of MACE, and large stent diameter and the use of drug-eluting stents were protective factors against MACE. The 2-year MACE rate beyond 1 month after AMI was significantly higher in DM patients than non-DM patients, and this rate was associated with higher comorbidities, coronary lesions, and procedural characteristics in DM.